LITERARY SUMMARY IN ARUNDHATI ROY’S THE GOD OF SMALL THINGS (International Journal of Food and Nutritional Sciences, 2022)
Arundhati Roy is an Indian female writer, alongside other Indian authors. Her aim is to creatively express herself in English. Literary fiction has been influenced by her novel The God of Small Things (1997) which was given the Booker Prize, one of the most prestigious awards in the book world. She works hard to perfect her craft. In the novel, the female psyche is depicted in great detail, using the protagonist's journey as a vehicle. Despite the fact that Arundhati Roy is not well-known, we all feel compelled to pay attention to what she has to say. An excellent writer, who is also an activist concerned with social and environmental issues. This organization stands in solidarity with the oppressed women and marginalized groups in society. The God of Small Things was met with sharply divergent public, literary, and journalistic responses in India, reviewers, and critics (125). A slightly serious woman-centered reading of the novel does in fact unveil several issues like women's limited access to property, bias in educational opportunities, and lack of equal human rights. It is up for debate whether or not post-colonial theory is legitimate. Post-colonial literature has increased its range by opening up floodgates. Both in themes and language, post-colonial literature can be identified as a kind of “subversion” or “resistance” to the imperialist “Center.” This research paper is an attempt to bring out the literary summary of the book, The God of Small Things.